Gut instinct: harnessing the power of probiotics to tame pathogenic signaling pathways in ulcerative colitis - Hsu, Chou-Yi; Mustafa, Mohammed Ahmed; Moath Omar, Thabit; Taher, Sada Gh; Ubaid, Mohammed; Gilmanova, Nataliya S.; Nasrat Abdulraheem, Mustafa; Saadh, Mohamed J.; Athab, Aya H.; Mirzaei, Rasoul; Karampoor, Sajad (Frontiers in Medicine, 2024)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) marked by persistent inflammation of the mucosal lining of the large intestine, leading to debilitating symptoms and reduced quality of life. Emerging evidence suggests that an imbalance of the gut microbiota plays a crucial role in UC pathogenesis, and various signaling pathways are implicated in the dysregulated immune response. Probiotics are live microorganisms that confer health benefits to the host, have attracted significant attention for their potential to restore gut microbial balance and ameliorate inflammation in UC. Recent studies have elucidated the mechanisms by which probiotics modulate these signaling pathways, often by producing anti-inflammatory molecules and promoting regulatory immune cell function. For example, probiotics can inhibit the nuclear factor-κB (NF-κB) pathway by stabilizing Inhibitor of kappa B alpha (IκBα), dampening the production of proinflammatory cytokines. Similarly, probiotics can modulate the Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway, suppressing the activation of STAT1 and STAT3 and thus reducing the inflammatory response. A better understanding of the underlying mechanisms of probiotics in modulating pathogenic signaling pathways in UC will pave the way for developing more effective probiotic-based therapies. In this review, we explore the mechanistic role of probiotics in the attenuation of pathogenic signaling pathways, including NF-κB, JAK/STAT, mitogen-activated protein kinases (MAPKs), Wnt/β-catenin, the nucleotide-binding domain (NOD)-, leucine-rich repeat (LRR)- and pyrin domain-containing protein 3 (NLRP3) inflammasome, Toll-like receptors (TLRs), interleukin-23 (IL-23)/IL-17 signaling pathway in UC.